2004
DOI: 10.1116/1.1813456
|View full text |Cite
|
Sign up to set email alerts
|

Inspection of templates for imprint lithography

Abstract: Articles you may be interested inResidual-type mask defect printability for extreme ultraviolet lithography J. Vac. Sci. Technol. B 30, 06F501 (2012); 10.1116/1.4756934 Sub-30 -nm patterning on quartz for imprint lithography templates Appl. Phys. Lett. 93, 083123 (2008); 10.1063/1.2963982Simple fabrication of UV nanoimprint templates using critical energy electron beam lithography Masks of any next generation lithography (NGL), such as imprint lithography, must eventually achieve and maintain the very low defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
(1 reference statement)
1
8
0
Order By: Relevance
“…Previous electron beam work established that programmed defects patterned on an ITO-based template can be calibrated in a CD SEM and inspected on a prototype e-beam inspection system of the KLA-Tencor eS30m [8,9]. The initial images Figure 8 (left) confirmed that these ITO templates are inspectable.…”
Section: Electron Beam Inspectionsupporting
confidence: 60%
“…Previous electron beam work established that programmed defects patterned on an ITO-based template can be calibrated in a CD SEM and inspected on a prototype e-beam inspection system of the KLA-Tencor eS30m [8,9]. The initial images Figure 8 (left) confirmed that these ITO templates are inspectable.…”
Section: Electron Beam Inspectionsupporting
confidence: 60%
“…With respect to inspection, although defects as small as 70 nm have been detected using optical techniques 9 , it is clear that it will be necessary to take advantage of the resolution capabilities of electron beam inspection techniques. Previous electron beam inspection work established that programmed defects patterned on an ITO-based template can be calibrated in a CD SEM and inspected on a prototype e-beam inspection system of the KLA-Tencor eS30m 10 .…”
Section: Protects Active Areamentioning
confidence: 99%
“…In the case of inspection, although defects as small as 70 nm have been detected using optical techniques, 9 it is clear that it will be necessary to take advantage of the resolution capabilities of electron beam inspection techniques. In the case of inspection, although defects as small as 70 nm have been detected using optical techniques, 9 it is clear that it will be necessary to take advantage of the resolution capabilities of electron beam inspection techniques.…”
Section: Introductionmentioning
confidence: 99%